1988
DOI: 10.1007/bf00174503
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of clomipramine in various brain regions of rats under steady-state serum concentrations

Abstract: The clomipramine (CMP) distribution in 12 regions of rat brain was investigated 2 and 7 days after subcutaneous minipump implantation. The results of serial blood samplings during 7 days indicated that steady-state CMP serum levels were achieved from experimental day 2. The regional CMP distributions in the brains were uneven on both the 2nd and 7th experimental days. On both test days the CMP concentrations were higher in the cerebral cortex and hippocampus than those in the other regions, and those in the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…As shown in table 2, the T/W ratio was the most appropriate for the present study, because only a study of the T/W ratio could clearly demonstrate both the uneven ATL distribution in the brain and the time X region interaction. There were uneven ATL distributions in the rat brains on the 2nd, 7th and 14th day, as shown in the previous studies of tricyclic antidepressants (TCAs) with single and/or multiple doses [7,11,16,20,25,27], The distribution pattern obtained in the present study generally resembled that of CMP [17], and was unlike the topographies of imipra mine binding sites and serotonin concentra tion in the brain [12]. There were significant differences in ATL levels between the 7th and 14th day in both ABG and PMO (ta ble 2).…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…As shown in table 2, the T/W ratio was the most appropriate for the present study, because only a study of the T/W ratio could clearly demonstrate both the uneven ATL distribution in the brain and the time X region interaction. There were uneven ATL distributions in the rat brains on the 2nd, 7th and 14th day, as shown in the previous studies of tricyclic antidepressants (TCAs) with single and/or multiple doses [7,11,16,20,25,27], The distribution pattern obtained in the present study generally resembled that of CMP [17], and was unlike the topographies of imipra mine binding sites and serotonin concentra tion in the brain [12]. There were significant differences in ATL levels between the 7th and 14th day in both ABG and PMO (ta ble 2).…”
Section: Discussionsupporting
confidence: 67%
“…It has been reported that in chronic intraperitoneal ATL administration the brain/plasma ratio for ATL reached 30 at 2 h after injection and fell to 8 at 12 h after the injection [3], It is therefore assumed that ADD brain/serum concentration ratios fluc tuate during the dosing interval and the ADD serum concentration may not reflect the steady-state brain concentration within the first week of medication, as mentioned above. Our previous study on 7-day contin uous infusion of CMP did not show any change in the CMP brain/serum concentra tion ratio [17], This may be due to some dif ference between the drugs or to the longer administration period in the present study. Glotzbach and Preskorn [14] reported that there was a linear correlation between the ATL concentrations in brain and serum in long-term ATL administration, and the brain/serum concentration ratio decreased in accordance with the increase in the ATL serum level.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations